Employee Performance Determination: The Effect of Transformational Leadership, Self-Efficacy, and Competence: Organizational Citizenship Behavior As A Mediating and Work Environment As A Moderating - Roif, Fadhil; Havidz Aima; Yulasmi, Yulasmi; Putra, Ramdani Bayu; Fitri, Hasmaynelis (UPI YPTK Journal of Business and Economics, 2024)
This study aims to analyze the determinants of employee performance through the influence of transformational leadership, self-efficacy, and competency, with Organizational Citizenship Behavior (OCB) as a mediating variable and the work environment as a moderating variable. The research was conducted at the Food and Drug Monitoring Agency (BBPOM) in Padang, West Sumatra. Data was collected through survey of BBPOM employees to assess the direct and indirect effects between these variables. The results show that transformational leadership, self-efficacy, and competency have a significant impact on employee performance, both directly and through the mediation of OCB. Furthermore, the work environment plays a crucial role in moderating the relationships between these variables. In conclusion, the combination of transformational leadership, self-efficacy, competency, OCB, and conduciveness work environment significantly enhance employee performance. This research contribute to the development of human resources management in the public sector, significantly in improving organizational performance through leadership and fostering organizational citizenship behavior